2013
DOI: 10.1109/tvlsi.2012.2231707
|View full text |Cite
|
Sign up to set email alerts
|

Hardware Designer's Guide to Fault Attacks

Abstract: Hardware designers invest a significant design effort when implementing computationally intensive cryptographic algorithms onto constrained embedded devices to match the computational demands of the algorithms with the stringent area, power and energy budgets of the platforms. When it comes to designs that are employed in potential hostile environments, another challenge arises: the design has to be resistant against attacks based on the physical properties of the implementation, the so-called implementation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
70
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(74 citation statements)
references
References 92 publications
0
70
0
Order By: Relevance
“…Low-cost fault attack either manipulates the clock or the power supply [15]. By lowering the supply voltage or increasing the clock frequency, the critical path should fail first.…”
Section: Security Analysis Against Dfamentioning
confidence: 99%
“…Low-cost fault attack either manipulates the clock or the power supply [15]. By lowering the supply voltage or increasing the clock frequency, the critical path should fail first.…”
Section: Security Analysis Against Dfamentioning
confidence: 99%
“…Research on FA techniques has been very active in both academic and industrial communities in the past twenty years and has revealed many exploitable design weaknesses for almost all cryptosystems families [6]. This has contributed to introducing new design practices to secure implementations against fault attacks for hardware designs [7] as well as software for embedded processors [8].…”
Section: Introductionmentioning
confidence: 99%
“…This is known as differential fault analysis (DFA). DFA has been demonstrated to be practical, and inexpensive [8,29]. Several DFAs have been shown by injecting clock glitches [2,7,47]; such shortening corrupts a single byte or multiple bytes.…”
Section: Introductionmentioning
confidence: 99%